Mnemotechnics of cruelty - Lucendo, Santiago (Re-visiones, 2024)
Starting from Maurizio Lazzarato’s reworking of the debtor/guilty concept developed by Nietzsche in his work On the Genealogy of Morality, the present article approaches the images that represent debt in the context of present capitalism. We will also see how debt and the indebted individual take part in a broader repertoire of images that, by their particular harshness and reference to the body, are easily taken in. These are the images that constitute the ‘mnemotechnics of cruelty’. But the same images that serve to consolidate the memory, or its elaborations in the domain of gothic horror fiction, can as well function in a critical sense. Here we are no longer talking about debt but of the use of art-horror images as part of a progressive machinery, or simply a liberating one, among which stands out the image of the vampire. The images used to denounce the abuses of capital establish, from the 18th century, the ‘gothic capitalism’: a vision of the modern world through images from another time.